2013
DOI: 10.11607/jomi.te35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proline-Rich Synthetic Peptide–Coated Titanium Implants on Bone Healing in a Rabbit Model

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…38 The only in vivo model assessing the bioactivity of P2 investigated the influence of P2 peptide-coated implants on bone healing. 19 P2 failed to promote osseointegration, although it is likely that the study was underpowered with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…38 The only in vivo model assessing the bioactivity of P2 investigated the influence of P2 peptide-coated implants on bone healing. 19 P2 failed to promote osseointegration, although it is likely that the study was underpowered with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the 45-amino acid fragment of amelogenin (TRAP) might be related to the observed early anti-inflammatory effect of EMD. In addition, in a rabbit model, Petzold et al 19 found a trend toward a reduced expression of genes related to pro-inflammatory cytokines and the osteoclastic marker tartrate-resistant acid phosphatase in bone tissue attached to P2-coated implants. 19 These observations require further studies to elucidate the mechanisms behind these in vivo effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyprolinreiche synthetische Peptide konnten die mRNA-Expression der Osteoblastenmarker Osteokalzin und Osteopontin steigern [84]. Eine Kaninchenstudie zeigte, dass die mRNA-Expression tartratresistenter saurer Phosphatase, eines Knochenabbaumarkers, signifikant reduziert war, während sich die Osteokalzinexpression im periimplantären Gewebe erhöh-te [85].…”
Section: Peptide Aus Knochenmatrixproteinenunclassified